38.4k views
19 votes
18x3 + 6x2y - 9x2 - 3xy

factor completely

2 Answers

10 votes

Answer:

6x2y(3xy2 − 1)

Explanation:

i got it right on my quiz :D

18x3 + 6x2y - 9x2 - 3xy factor completely-example-1
User Zeni
by
5.6k points
4 votes

Answer:


\sf 3x(3x+y)(2x-1)

Explanation:

Given expression:


\sf 18x^3 + 6x^2y - 9x^2 - 3xy

Factor out common term
\sf 3x:


\sf \implies 3x(6x^2 + 2xy - 3x - y)

Factor
\sf (6x^2 + 2xy - 3x - y)

Rearrange:


\sf \implies 6x^2 - 3x+ 2xy - y

Factor pairs of terms:


\sf \implies 3x(2x-1)+ y(2x - 1)

Factor out common term (2x - 1):


\sf \implies (3x+y)(2x-1)

Final solution:


\sf \implies 3x(3x+y)(2x-1)

User Adrian Ancuta
by
6.1k points